ANALISIS PENGELOLAAN ASET DALAM MENDUKUNG OPERASIONAL PELAYANAN DI MAL PELAYANAN PUBLIK KOTA CIMAHI - Hermawati, Ema; Afandi, Muhamad Nur; Yustiono, Eris; Kurniawan, Iwan (Program Studi Administrasi Publik, FISIP, Universitas Tulang Bawang Lampung, 2025)
Asset management is one of the important aspects in supporting the operational services at the Public Service Mall (MPP) of Cimahi City as a center for integrated services for the community. This research aims to analyze asset management at the MPP of Cimahi City. The research method used is descriptive qualitative with data collection techniques through interviews, observations, and documentation studies. The analysis is conducted using the asset management theory approach according to Siregar which includes five indicators: asset inventory, legal audit, asset valuation, asset optimization, and supervision and control. The results of the study indicate that asset management at the MPP of Cimahi City is already functioning quite well. However, several constraints were found, namely the presence of assets in several tenants that do not have asset inventory labeling, in addition, the inventory data regarding asset damage and loss is still minimal, and there are assets that have not been optimally utilized. The conclusion of this study is that asset management in the MPP of Cimahi City has generally supported operational services, but there are still constraints in the aspects of asset inventory and asset optimization. To address this, a digital reporting system is needed to record asset damage or loss in real time. Additionally, it is necessary to prepare clear and structured Standard Operating Procedures (SOP) regarding the management of regional-owned goods. The next effort involves socialization and education for tenant officers and related parties involved in asset management, including technical training in the operation of certain assets. Keywords: Asset Management; Public Service Mall; Service Operation